Efficacy of allogeneic mesenchymal stem cell administration in a model of acute ischemic kidney injury in cats. (October 2016) - Rosselli, Desiree D.; Mumaw, Jennifer L.; Dickerson, Vanna; Brown, Cathy A.; Brown, Scott A.; Schmiedt, Chad W.
Abstract: Objective: To evaluate the effects of allogeneic mesenchymal stem cells (MSCs) in a model of ischemic acute kidney injury (AKI). Study design: Randomized controlled trial. Animals: Adult, purpose-bred research cats (n = 15) and a historical reference group (n = 3). Methods: Cats underwent unilateral, in vivo, warm renal ischemia, then intravenous administration of 4 million adipose-derived MSCs, bone marrow-derived MSCs, or fibroblasts (n = 5/treatment) 1 h after reperfusion. Serum creatinine and blood urea nitrogen concentrations were measured at baseline and days 1 and 6. Urine specific gravity, urine protein to urine creatinine ratio, and glomerular filtration rate were measured at baseline and day 6. Both kidneys were harvested on day 6; histopathology was described and scored and smooth muscle actin was quantified with histomorphometry. A 2-way ANOVA was used to compare time and treatment. Chi square analysis was used to determine the % of cats with at least International Renal Interest Society (IRIS) Grade 1 AKI. Results: Time, but not treatment, had a significant effect on renal function. No difference was noted in % of cats with IRIS AKI. Significantly fewer mitotic figures were observed in ischemic kidneys that received bone-marrow derived MSCs vs. fibroblasts. No differences in smooth muscle actin staining were noted. Conclusions: This study did not support the use of allogeneic MSCs in AKI in the regimen described here. Type of renal injury, MSC dose, allogenicity, duration, and route or timing of administration could influence the efficacy MSCs. Highlights: A described model was used to induce acute kidney injury in cats. Fat and bone marrow derived MSCs were tested to reduce acute kidney injury. No differences in renal function or histomorphometry were observed. Bone marrow derived MSCs caused reduction in mitotic figures. Modification in dose, route, or frequency may improve efficacy.